Language management and its impact - Li, Linda Mingfang. ([Place of publication not identified])
1 online resource
Keywords: This book provides a comprehensive account of language management and planning at Confucius Institutes in the UK, implementing an ethnographic approach grounded in language management theory. As a global language promotion organization, Confucius Institutes have previously been discussed in the literature with respect to socio-political issues, but this volume will shed particular light on their role in shaping and informing Chinese language policy, at both the institutional and individual classroom level. The book focuses specifically on Confucius Institutes in the UK, demonstrating how language teaching practice in these organizations is informed and shaped not only by organizational paradigms but local language needs and institutional attitudes of host institutions. In turn, Li highlights these organizations' unique position in a multilingual region such as the UK can offer new insights into language management by illustrating their roles as platforms for both individuals and institutions to become involved in the making and implementation of language policy. This volume will be of particular interest to students and researchers in language policy and planning, language education, applied linguistics, and Chinese linguistics.